THE INTERGENERATIONAL UNDERSTANDING AND USE LEVEL OF BAMBOO AND COCONUT TREE LEXICONS IN THE SPEECH COMMUNITY OF USING - Sarmi, Ni Nyoman; Mbete, Aron Meko; Putra Yadnya, Ida Bagus; Padmadewi, Ni Nyoman (e-Journal of Linguistics; 2016: Vol 10. No. 1 January)
The study is aimed at describing the level of understanding and use of the bamboo and coconut tree lexicons which refer to both the entity and its derivatives by Using ethnic community and the factors that become the background. To cope with the research problems ecolinguistic theory was applied. The data were collected by using observation, interview and documentation methods supported by recording technique and questionnaires. Results of the data analysis are presented with formal and informal methods of deductive and inductive techniques, The results of analysis indicate that the level of respondents’ understanding and use on the lexicons of bamboo and coconut trees vary. The level of understanding and use of these two generic lexicons reaches 100% for all respondents while for specific lexicons and its derivatives, the understanding and use seem to vary. The lexicons which reference entities have a high usefulness, interaction, interrelation and interdependency, the level of understanding and use is also high. Inspite of its numerous entity population, the population of entities seem much but if the lexicon does not have the benefit on the lives of the respondents, the level of understanding of the lexicon can be high but usage levels are low, particularly for juvenile respondents. In addition, there are a number of lexicon with a usage rate of 0% among the juvenile respondents. It happened on the lexicon of equipment made of bamboo which has a rare or endangered reference entity because its function is replaced by another entity. Meanwhile, the factors that cause differences in the level of intergenerational understanding and use level of the lexicon of bamboo and coconut trees include (1) little population of entities; (2) less interaction, interrelation and interdependence on the reference entities; (3) some UL lexicon are replaced by other language lexicons; (4) the absence of  transfer of knowledge of the reference entity from the predecessor generation;  (5) the function of the reference entity is replaced by another entity function; and (6) the level of understanding and use of the respondent only at the level of generic lexicon.
Keywords: lexicon, interaction, interrelation, interdependence, level of understanding and level of use